KNITTING EFFICIENT LEARNING BEHAVIOR: AN ISLAMIC EDUCATIONAL PSYCHOLOGY PERSPECTIVE - Tryani; Mahenra, Tegar; Aminullah (Qawwam : The Leader's Writing, 2025)
This study aims to comprehensively examine the concept of learning behavior from the perspective of Islamic educational psychology through the implementation of library research methods with a qualitative approach. Relevant data were analyzed using content analysis techniques on various literature sources, including scientific journal articles, theses, dissertations, and books related to the research topic. The data collection process involved a systematic search of leading electronic databases. This descriptive analytical study seeks to deeply explore and synthesize existing understandings of learning behavior within the framework of Islamic educational psychology. The findings of the analysis reveal that learning behavior in this perspective is not limited to cognitive aspects alone, but integrally includes spiritual, moral, and social dimensions that are in line with Islamic values. Efficiency in learning is influenced by internal factors (such as sincere intentions, spiritual intelligence, and intrinsic motivation) and external factors (including the learning environment, teaching methods applied, and social support). In addition, effective time management is also considered a crucial element in improving learning efficiency. Various learning approaches and methods in Islamic psychology are designed to achieve a holistic understanding of Islamic teachings and stimulate the development of critical thinking skills and spiritual dimensions in students.